Towards Targeted MRI: New MRI Contrast Agents for Sialic Acid Detection - Frullano, Luca; Rohovec, Jan; Aime, Silvio; Maschmeyer, Thomas; Prata, M. Isabel; de Lima, J. J. Pedroso; Geraldes, Carlos F. G. C.; Peters, Joop A. (Chemistry : a European journal, 2004)
The detection of sialic acid in living systems is of importance for the diagnosis of several types of malignancy. We have designed and synthesized two new lanthanide ion ligands (L1 and L2) that are capable of molecular recognition of sialic acid residues. The basic structure of these ligands consists of a DTPA‐bisamide (DTPA, diethylenetriamine pentaacetic acid) whose amide moieties each bear both a boronic function for interaction with the diol groups in the side chain of sialic acid, and a functional group that is positively charged at physiologic pH values and is designed to interact with the carboxylate anion of sialic acid. The relaxometric properties of the Gd3+ complexes of these two ligands were evaluated. The relaxivity of the GdL1 complex has a significant second‐sphere contribution at pH values above the pKa of its phenylboronic acid moiety. The interaction of the Gd3+ complexes of L1 and L2 with each of several saccharides was investigated by means of a competitive fluorescent assay. The results show that both complexes recognize sialic acid with good selectivity in the presence of other sugars. The adduct formed by GdL2 with sialic acid has the higher conditional formation constant (50.43±4.61 M−1 at pH 7.4). The ability of such complexes to recognize sialic acid was confirmed by the results of a study on the interaction of corresponding radiolabeled complexes (153SmL1 and 153SmL2) with C6 glioma rat cells. 153SmL2 in particular is retained on the cell surface in significant amounts. Selective molecular recognition of N‐acetylneuraminic acid residues (Neu5Ac; see scheme) on cell walls was achieved by the lanthanide complexes of two DTPA‐bisamide ligands (L1 and L2). Both ligands were designed with boronate functions that recognize the diol group in the side chain of Neu5Ac, and positively charged functions that interact with the Neu5Ac carboxylate group.